Ovarian Hormone-Dependent Effects of Dietary Lipids on APP/PS1 Mouse Brain - Herrera, Jose Luis; Ordoñez-Gutierrez, Lara; Fabrias, Gemma; Casas, Josefina; Morales, Araceli; Hernandez, Guadalberto; Acosta, Nieves G.; Rodriguez, Covadonga; Prieto-Valiente, Luis; Garcia-Segura, Luis M.; Wandosell, Francisco G.; Alonso, Rafael (Frontiers in Aging Neuroscience, 2019)
The formation of senile plaques through amyloid-ß peptide (Aß) aggregation is a hallmark of Alzheimer's disease (AD). Irrespective of its actual role in the synaptic alterations and cognitive impairment associated with AD, different therapeutic approaches have been proposed to reduce plaque formation. In rodents, daily intake of omega-3 (n-3) long-chain polyunsaturated fatty acids (LC-PUFAs) is required for neural development and there is experimental and epidemiological evidence that their inclusion in the diet has positive effects on several neurodegenerative diseases. Similarly, estradiol appears to reduce senile plaque formation in primary mouse cell cultures, human cortical neurons and mouse AD models, and it prevents Aß toxicity in neural cell lines. We previously showed that differences in dietary n-6/n-3 LC-PUFAs ratios modify the lipid composition in the cerebral cortex of female mice and the levels of amyloid precursor protein (APP) in the brain. These effects depended in part on the presence of circulating estradiol. Here we explored whether this potentially synergistic action between diet and ovarian hormones may influence the progression of amyloidosis in an AD mouse model. Our results show that a diet with high n-3 LC-PUFA content, especially DHA (22:6n-3), reduces the hippocampal accumulation of Aß1-40, but not amyloid Aß1-42, in female APPswe/PS1 E9A mice, an effect that was counteracted by the loss of the ovaries and that depended on circulating estradiol. In addition, this interaction between dietary lipids and ovarian function also affects the composition of the brain lipidome, as well as the expression of certain neuronal signaling and synaptic proteins. These findings provide new insights into how ovarian hormones and dietary composition affect the brain lipidome and amyloid burden. Furthermore, they strongly suggest that the when designing dietary or pharmacological strategies to combat human neurodegenerative diseases, hormonal and metabolic status should be specifically taken into consideration as it may affect the therapeutic response.